Authorship structure of scholarly disciplines an empiirical study of Philippine research journals - De La Torre, Nathalie N. (2006)
This study was conducted to find out whether Lotka's law of scientific productivity applies to selected Filipiniana research journals. The theory of absolute and relative concentration was also tested to prove that as the sample size increases, relative concentration also increases. Authorship in the Sciences, Social Sciences, and Humanities disciplines were also delved into, as well as comparison of authorship in the hard and soft sciences. A comparison between pure and applied science was also done by comparing a journal title in mathematics with selected journals in science, medicine, biotechnology, engineering, and economics.